Clinical findings of autosomal-dominant striatal degeneration and PDE8B mutation screening in parkinsonism and related disorders. (December 2019) - Ni, Jie; Yi, Xiaoping; Liu, Zhen; Sun, Weining; Yuan, Yanchun; Yang, Jie; Jiang, Hong; Shen, Lu; Tang, Beisha; Liu, Yunhai; Wang, Junling
Abstract: Background: Autosomal-dominant striatal degeneration (ADSD) is a rare neurodegenerative movement disorder caused by mutations in the Phosphodiesterase 8B ( PDE8B ) gene. Objective: To summarize the clinical and imaging features of a Chinese ADSD family and determine whether mutations in PDE8B are associated with Parkinson's disease (PD) or Parkinsonism. Methods: Clinical, imaging and genetic findings in a Chinese ADSD family are reported. Rare, potentially pathogenic variants in PDE8B were searched in whole-exome sequencing datasets from 1714 PD or parkinsonism patients and 1039 controls. Results: An ADSD diagnosis was confirmed by a nonsense mutation in PDE8B (p.E102X) in a patient and a presymptomatic carrier. Clinically, the patient exhibited progressive parkinsonism without tremor and ataxia phenotype. Neuroimaging showed an inhomogeneous increased signal in the patient's striatum on T1-weighted images but a decreased signal in the presymptomatic carrier. Diffusion tensor imaging (DTI) showed a disturbance in the white matter fiber distribution, especially between the lentiform nucleus and caudate nucleus, which was more prominent in the patient than in the presymptomatic carrier. Within the 1714 patients, three PDE8B missense variants were identified that were unlikely to be the cause of the parkinsonism phenotype according to the functional prediction and mutation types reported in ADSD. Conclusions: For the first time, we described the typical ataxia phenotype in ADSD. A loss of white matter fiber integrity was shown on DTI scanning. No causative PDE8B mutation was discovered in our cohort of PD or Parkinsonism patients. Highlights: For the first time, reported the typical ataxia phenotype in ADSD. DTI images showed a loss of white matter fiber integrity. No causative PDE8B mutation was discovered in parkinsonism and related disorders.